Bird Species Composition in Ayer Hitam Forest, Puchong, Selangor - Mohamed Zakaria,; Abdul Rahim, (Universiti Putra Malaysia Press, 1999)
This study focused on the avian species composition in Ayer Hitam Forest, Puchong, Selangor. The forest is an isolated secondary lowland forest and was logged between 1936 to 1954. Two methods were used to examine the composition of birds in the area namely by Mist-netting and Distance Sampling-Point Count. Results indicated that a total of 38 families which comprised of 160 species of birds have been recorded. The three biggest families that represent about 23.5 percent of the total species are Timaliidae, Cuculidae and Pycnonotidae. The most common individuals recorded belong to the family Pycnonotidae. The forest is dominated by insectivore/frugivore group which is represented by mainly colonising secondary species. Certain species of hornbills (e.g. Buceros rhinoceros) and babblers (e.g. Pomatorhinus montanus) that are normally found in primary forest are absent. These results suggested that the composition offamilies and trophic structures of birds in Ayer Hitam Forest Reserve are comparable with those at other forest reserve areas. However, the absence of many primary forest species suggested that the forest is still under recovering process. It is recommended that the major part of the forest is left undisturbed to prevent the few remaining wild life habitats from further destruction and to allow the wildlife species composition to return to the original condition.